Organized labor versus robots? Co-determination in times of automation - Sebastian Findeisen; Wolfgang Dauth; Oliver Schlenker (EconPol Forum, 2025)
Works councils reduce job separations during automation events, especially when firms can easily replace incumbent workers. Among workers who are most prone to automation, works councils prevent wage and earnings losses when firms adopt robots. Works councils prevent earnings inequality through automation to rise by limiting earnings gains for non-production workers. Plants with works councils accompany robot adoption with more training and experience higher productivity levels thereafter. These results suggest that labor market institutions can benefit both incumbent workers and firms.
Keywords: 330